Community-Based Preaching Model in Preventing Online Radicalization among Adolescents - Hapsari, Twediana Budi; Rhafidilla, Vebrynda; Muzayana, Muzayana (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
Adolescence is a period that is vulnerable to being influenced by radicalism due to the psychological development of adolescents still looking for their identity. Therefore, at this stage, they are unstable, and their emotional condition opens opportunities for the entry of various new ideas - including radicalism. Meanwhile, today's adolescents are also known as a generation that is very close to the internet, so they are very vulnerable to being exposed to this online radicalism. This research tried to find a community-based da'wah model to prevent the spread of online radicalization among adolescents in Aceh, Bali, and Lamongan. Data was taken through a focus group discussion, which included government elements, educators, religious leaders, and academics working in the field of youth radicalism. The results show that this effort requires the cooperation of at least four institutions in society - apart from the government - namely the family, educational institutions, social systems, and Islamic mass organizations. Hopefully, these four elements in society can detect and provide the correct direction for adolescents to access religious content on the internet.